Bayesian Meta-analysis of Direct Oral Anticoagulation Versus Vitamin K Antagonists With or Without Concomitant Antiplatelet After Transcatheter Aortic Valve Implantation in Patients With Anticoagulation Indication. (July 2023) - Lee, Gabriel Sheng Jie; Tay, Hannah Si En; Teo, Vanessa Xin Yi; Goh, Rachel Sze Jen; Chong, Bryan; Chan, Siew Pang; Tay, Edgar; Lim, Yinghao; Yip, James; Chew, Nicholas W. S; Kuntjoro, Ivandito
Patients undergoing transcatheter aortic valve implantation (TAVI) commonly have co-morbidities requiring anticoagulation. However, the optimal post-procedural anticoagulation regimen is not well-established. This meta-analysis investigates safety and efficacy outcomes of direct oral anticoagulants (DOACs) and Vitamin K Antagonist (VKA), with or without concomitant antiplatelet therapy. We searched EMBASE and MEDLINE for appropriate studies. Subgroup analyses were performed for anticoagulant monotherapy and combined therapy with antiplatelet agents. Eleven studies (6359 patients) were included. Overall, there were no differences between DOACs and VKA for all-cause mortality (Odds Ratio [OR]: .69; Credible Interval [CrI]: .40–1.06), cardiovascular-related mortality (OR: .76; Crl: .13–3.47), bleeding (OR: .95; CrI: .75–1.17), stroke (OR: 1.04; CrI: .65–1.63), myocardial infarction (OR: 1.51; CrI: .55–3.84), and valve thrombosis (OR: .29; CrI: .01–3.54). For DOACs vs VKA monotherapy subgroup, there were no differences in outcomes. For the combined therapy subgroup, there was decreased odds of all-cause mortality in the DOACs group compared with the VKA group (OR: .13; CrI: .02–.65), but no differences for bleeding and stroke. DOACs and VKA have similar safety and efficacy profiles for post-TAVI patients with anticoagulation indication. However, if concomitant antiplatelet therapy is required, DOACs were more favorable than VKA for all-cause mortality.